Environmental health science : recognition, evaluation, and control of chemical and physical health hazards - Lippmann, Morton (Oxford University Press, 2003)
This is a broad, in-depth introduction to a scientific field that is becoming ever more central to human health. Environmental exposures to a bewildering array of chemical and physical agents result from our individual and collective activities, and can cause effects ranging from discomfort through loss of function, illness, chronic diseases, and premature death. Their concomitant effects on quality of life, productivity, and need for clinical services can be costly. The book covers the terminology used in environmental health; the sources of chemical and physical agents in the environment; how they disperse and transform throughout the environment; their effects on environmental quality and human health; how levels and exposures are quantified; how standards are established; how levels, exposures, and risks can be controlled; and what technological opportunities and trends are likely to influence our environmental future. It includes chapters on noise, ionizing radiation, non-ionizing radiation, risk assessment, and risk management. Written in a clear and systematic way, this text will be an invaluable resource for students of environmental health.; An earlier version of the book, Chemical Contamination in the Human Environment (OUP 1979), was called by one teacher "visionary ... easily the most useful textbook in environmental health science for entry-level graduate students.